NMDAR1-Src-Pannexin1 Signal Pathway in the Trigeminal Ganglion Contributed to Orofacial Ectopic Pain Following Inferior Alveolar Nerve Transection. (1st July 2021) - Li, Yue-ling; Liu, Fei; Zhang, Yan-yan; Lin, Jiu; Huang, Chao-lan; Fu, Min; Zhou, Cheng; Li, Chun-jie; Shen, Jie-fei
Graphical abstract: Highlights: We explored the effects of NR1, Src, and Panx1 in the TG on orofacial ectopic pain following IANX. We demonstrated that inhibition of NR1, Src, or Panx1 could relieve the ectopic pain. We suggested that NR1, Src, and Panx1 composed a signal pathway in the TG involved in the pain. Abstract: The N-methyl-d -aspartate receptor (NMDAR) is a glutamate-gated receptor channel that plays a role in peripheral neuropathic pain. Src, a protein tyrosine kinase, can regulate the activation of NMDARs in chronic pain conditions. Pannexin 1 (Panx1), a plasma membrane channel, plays an important role in neuropathic pain and functionally interacts with NMDARs in the pathological condition of epilepsy. In this study, the roles of NMDAR1 (NR1), Src, and Panx1 and their interactions in the trigeminal ganglion (TG) in orofacial ectopic pain attributed to inferior alveolar nerve transection (IANX) were investigated. IANX induced mechanical allodynia in the whisker pad with increased expression levels of NR1, Src phosphorylation (p-Src), and Panx1 in the TG. Double immunostaining revealed that NR1, Src, and Panx1 all colocalized with glutamine synthetase (GS) and neuronal nuclei (NeuN), and they overlapped in the TG, suggesting that they might be structurally connected to one another. In addition, trigeminal injection of memantine, PP2, or 10 Panx attenuated IANX-induced mechanical allodynia in the whisker pad. Continuous intraganglionic administration of memantine (an antagonist of NMDAR) decreased IANX-induced upregulated expression of p-Src and Panx1. Similarly, PP2 (an inhibitor of Src) also decreased Panx1 protein expression but had no effect on NR1. In addition, intraganglionic injection of 10 Panx (a blocker of Panx1) decreased NR1 protein expression but did not affect Src. In general, our findings demonstrated that NR1, Src, and Panx1 all contributed to orofacial ectopic pain following IANX and that they composed a signalling pathway in the TG involved in mechanical allodynia.